2020
DOI: 10.1093/ehjcr/ytaa339
|View full text |Cite
|
Sign up to set email alerts
|

A case report of multisite arterial thrombosis in a patient with coronavirus disease 2019 (COVID-19)

Abstract: Background A systemic coagulation dysfunction has been associated with COVID-19. In this case report, we describe a COVID-19-positive patient with multisite arterial thrombosis, presenting with acute limb ischaemia and concomitant ST-elevation myocardial infarction and oligo-symptomatic lung disease. Case summary An 83-year-old lady with history of hypertension and chronic kidney disease presented to the Emergency Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Previous studies support this finding. Reports also showed an increased risk of thrombosis in patients with a history of cardiovascular disease and stroke, as well as hypertension and diabetes [ 27 ]. Surprisingly, patients may develop extensive thrombosis even if they have no such medical comorbidities [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies support this finding. Reports also showed an increased risk of thrombosis in patients with a history of cardiovascular disease and stroke, as well as hypertension and diabetes [ 27 ]. Surprisingly, patients may develop extensive thrombosis even if they have no such medical comorbidities [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination modelling for safe surgeries and identification of timing of surgery in COVID-19 patients are currently under investigation [5]. However, some authors have reported atypical clinical presentations, such as cardiac or neurological involvement [6]. In literature are reported several cases of stent thrombosis in positive COVID-19 patients after coronary procedure but are not reported cases about stent thrombosis in peripheral artery [7].…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente se ha asociado a una respuesta sistémica procoagulante, la cual es multifactorial (1).…”
Section: Introductionunclassified